Redesigned Sensor Holder for an Atomic Force Microscope with an Adjustable Probe Direction - Schaude, Janik; Fimushkin, Maxim; Hausotte, Tino (International Journal of Precision Engineering and Manufacturing, 2021)
The article presents a redesigned sensor holder for an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, consisting of a commercial piezoresistive cantilever operated in closed-loop intermitted contact-mode, is based on two rotational axes, which enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion. The AFM is therefore operated within a thermostating housing with a long-term temperature stability of 17 mK. The sensor holder, connecting the rotational axes and the cantilever, inserted one adhesive bond, a soldered connection and a geometrically undefined clamping into the metrology circle, which might also be a source of measurement error. It has therefore been redesigned to a clamped senor holder, which is presented, evaluated and compared to the previous glued sensor holder within this paper. As will be shown, there are no significant differences between the two sensor holders. This leads to the conclusion, that the three aforementioned connections do not deteriorate the measurement precision, significantly. As only a minor portion of the positioning range of the piezoelectric actuator is needed to stimulate the cantilever near its resonance frequency, a high-speed closed-loop control that keeps the cantilever within its operating range using this piezoelectric actuator further on as actuator was implemented and is presented within this article.<br
Keywords: Atomic force microscopy; Tilting-AFM; Piezoresistive cantilever; Nano measuring machine